Multimodal cross‐examination of progressive apraxia of speech by diffusion tensor imaging‐based tractography and Tau‐PET scans - Gatto, Rodolfo G.; Pham, Nha Trang Thu; Duffy, Joseph R.; Clark, Heather M.; Utianski, Rene L.; Botha, Hugo; Machulda, Mary M.; Lowe, Val J.; Schwarz, Christopher G.; Jack, Clifford R.; Josephs, Keith A.; Whitwell, Jennifer L. (Human brain mapping, 2024)
Progressive apraxia of speech (PAOS) is a 4R tauopathy characterized by difficulties with motor speech planning. Neurodegeneration in PAOS targets the premotor cortex, particularly the supplementary motor area (SMA), with degeneration of white matter (WM) tracts connecting premotor and motor cortices and Broca's area observed on diffusion tensor imaging (DTI). We aimed to assess flortaucipir uptake across speech‐language‐related WM tracts identified using DTI tractography in PAOS. Twenty‐two patients with PAOS and 26 matched healthy controls were recruited by the Neurodegenerative Research Group (NRG) and underwent MRI and flortaucipir‐PET. The patient population included patients with primary progressive apraxia of speech (PPAOS) and non‐fluent variant/agrammatic primary progressive aphasia (agPPA). Flortaucipir PET scans and DTI were coregistered using rigid registration with a mutual information cost function in subject space. Alignments between DTI and flortaucipir PET were inspected in all cases. Whole‐brain tractography was calculated using deterministic algorithms by a tractography reconstruction tool (DSI‐studio) and specific tracts were identified using an automatic fiber tracking atlas‐based method. Fractional anisotropy (FA) and flortaucipir standardized uptake value ratios (SUVRs) were averaged across the frontal aslant tract, arcuate fasciculi, inferior frontal‐occipital fasciculus, inferior and middle longitudinal fasciculi, as well as the SMA commissural fibers. Reduced FA (p < .0001) and elevated flortaucipir SUVR (p = .0012) were observed in PAOS cases compared to controls across all combined WM tracts. For flortaucipir SUVR, the greatest differentiation of PAOS from controls was achieved with the SMA commissural fibers (area under the receiver operator characteristic curve [AUROC] = 0.83), followed by the left arcuate fasciculus (AUROC = 0.75) and left frontal aslant tract (AUROC = 0.71). Our findings demonstrate that flortaucipir uptake is increased across WM tracts related to speech/language difficulties in PAOS. Structural connectomics assessment of the supplementary motor area (SMA) in progressive apraxia of speech (PAOS) subjects. White matter connectivity representation from cortical regions involved in the language network (LN) shows lower fractional anisotropy (FA) and larger mean diffusivity (MD) and standardized uptake value ratio (SUVR) values than control. The addition of SMA to the speech and LN demonstrates further FA decrease in MD and SUVR increase likely due to the involvement of SMA in the disease.